An Effective and Secure Access Control System Scheme in the Cloud. Issue 3 (1st July 2015) - Niu, Shaozhang; Tu, Shanshan; Huang, Yongfeng
Abstract : Cloud computing services have got rapid development in the field of the light weight terminal, especially wireless communications. The comprehensive access control system framework is proposed for the cloud. A kind of access control scheme based on attribute encryption isdesigned, in which light weight devices can safely use cloud computing resources to outsource encrypt/decrypt operations, and not worry for exposing terminal sensitive data. The scheme is verified by performance evaluation about the security, computing, storage, to ensure the legitimate interests of users in the cloud.